2007
DOI: 10.3844/ajassp.2007.1016.1023
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Grasping Contact Analysis of Biological Tissues With Applications in Minimally Invasive Surgery

Abstract: Analytical and finite element methods are employed to determine the contact pressure on the surface of a tissue being grasped by an endoscopic grasper, in Minimally Invasive Surgery (MIS). Normally, an endoscopic grasper is corrugated (teeth-like) in order to grasp slippery tissues. It is highly important to avoid damage to the tissues while grasping and manipulation during endoscopic surgery. Therefore, it is essential to determine the exact contact pressure on the surface of the tissue. To this end, initiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In addition, it has been suggested that EPO can increase red blood cells leading to a reduction in cellular oxidative stress. According to the literature, EPO also exerts its beneficial effect in ischemic organs by prevention of apoptosis, probably by increasing Bcl2 and HSP70 expression Bonakdar et al, 2007). The time which the tissue exposing to ischemia is critical.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, it has been suggested that EPO can increase red blood cells leading to a reduction in cellular oxidative stress. According to the literature, EPO also exerts its beneficial effect in ischemic organs by prevention of apoptosis, probably by increasing Bcl2 and HSP70 expression Bonakdar et al, 2007). The time which the tissue exposing to ischemia is critical.…”
Section: Discussionmentioning
confidence: 99%
“…In their study reduction of medium oxygen content to <1% triggered a majority of cells to enter in apoptosis. It appears that the ovaries have high resistance to ischemia (Ming et al, 2001;Bonakdar et al, 2007). EPO is a protective tissue cytokine it's receptors have been shown to exist in lots of tissues.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations